2012
DOI: 10.1111/j.1442-2050.2012.01418.x
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable stents for caustic esophageal strictures: a new therapeutic approach

Abstract: The treatment of caustic esophageal strictures is a challenging topic. Although traditional therapies have limited efficacy, most of these patients eventually require surgery. Biodegradable (BD) stents are newly designed stents for benign conditions. This is a retrospective case series of seven patients with caustic esophageal stricture. BD esophageal stents were inserted for palliation of dysphagia. The position of the stent was checked at 1, 4, 8, 12 16, 20, and 24 weeks and at the end of follow-up period. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 10 publications
0
14
0
5
Order By: Relevance
“…Retrosternal chest pain reflects the process of stent deployment in order to achieve its planned diameter. The pain is usually self-limited; however, analgesics, including opioids, may be required to control it [41]. Rarely, the pain may persist for a long period of time or may be not tolerated by the patient, leading to early stent removal to relieve the patient's symptoms.…”
Section: Safety Outcomes -Complicationsmentioning
confidence: 99%
“…Retrosternal chest pain reflects the process of stent deployment in order to achieve its planned diameter. The pain is usually self-limited; however, analgesics, including opioids, may be required to control it [41]. Rarely, the pain may persist for a long period of time or may be not tolerated by the patient, leading to early stent removal to relieve the patient's symptoms.…”
Section: Safety Outcomes -Complicationsmentioning
confidence: 99%
“…Our systematic review of 111 patients with a benign esophageal stricture obtained from nine studies showed the following results: technical success rate of 96%, clinical success rate of 47%, early stent migration rate of 21%, and tissue hyperplasia rate of 13% (Table 3). 12,21,30,32,33,34,35,39,40…”
Section: Biodegradable Stentmentioning
confidence: 99%
“…In contrast to the advances in materials and technology, there is absence of specially designed esophageal SEMSs for children regarding their age and size. Therefore, stents that are made from different materials [9,10,16,24] and originally designed for other organs are used as an "off-label technique" in the pediatric population [7,9,18,23]. In this study, the number of stents ranged between one and three different biliary and/or bronchial SEMSs that were successively placed.…”
Section: Discussionmentioning
confidence: 99%